JARINGAN SOSIAL PETANI DALAM PENGEMBANGAN USAHATANI LAHAN PANTAI DI KECAMATAN PANJATAN KABUPATEN KULON PROGO - , Dani Kurniawan ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research was conducted to identify the social networks of farmers in the development of coastal land farming. Subjects of this research were 60 respondents, that were all coastal land farmer. Basic methods were descriptive analytic method and explanative. The data was collected through observation techniques, interviews and records. Statistic methods were proportion test, analysis of the cohesion index, chi square analysis and gamma test. Researchâs findings indicated : (1) farmerâs social network was strong both in technical and untechnical farming activities, (2) farmerâs social network was tend to be large in technical farming activities, (3) farmerâs social network was tend to be cohesive in technical farming activities, (4) motivation that being spirit to gain success significanly affected social network of farmer.